52. SEDATIVE AND ANALGESIC ACTIVITY OF NEPETA CATARIA L. (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the sedative and analgesic effects of aqueous and 99% ethanol extracts from Nepeta cataria L.Materials  and  methods: The sedative-anxiolytic effects were evaluated using the pentobarbital-induced sleeping test and the light-dark box test. The analgesic effects were assessed through the acetic acid-induced writhing test in C57BL/6 mice.Results: The Nepeta cataria ethanol extract at a dose of 162 mg/kg demonstrated sedative-anxiolytic effects by prolonging pentobarbital-induced sleeping time and increasing the time spent in the light area, with effects comparable to Diazepam (1 mg/kg). Additionally, the 162 mg/kg ethanol extract exhibited analgesic effects by reducing the number of writhings induced by acetic acid which was similar to the effect of diclofenac potassium (15 mg/kg).Conclusion: Oral administration of the Nepeta cataria ethanol extract at 162 mg/kg demonstrated sedative and analgesic effects in mouse models. The aqueous extract at 70 mg/kg did not exhibit significant effects in the conducted experiments.
Keywords: Sedation; anesthesia; hot–plate test; light–dark box test; Nepeta cataria